Clinical Significance of Quantitative HBs Antigen in the Prediction of Liver Fibrosis in Patients with Chronic Hepatitis B - Dimzova, Marija; Kondova Topuzovska, Irena; Milenkovikj, Zvonko; Gaseva, Magdalena; Chaloska Ivanova, Viktorija; Serafimoski, Vladimir; Orovchanec, Nikola (Macedonian Academy of Sciences and Arts, 2018)
The assessment of liver fibrosis in patients with chronic hepatitis B (CHB) is of great importance in evaluating the phases of chronic hepatitis B viral infection, prompt administration of antiviral therapy, prevention of disease progression and late complications of CHB infection. Aim: to investigate the clinical significance of quantitative HBs antigen as a predictor for liver fibrosis in patients with HBe antigen negative chronic hepatitis B and inactive carriers. Material and Methods: the study included 44 treatment naïve patients with chronic hepatitis B, divided into two groups, HBeAg negative chronic HBV infection or inactive carriers (IC) and HBeAg negative chronic hepatitis B patients. All patients underwent laboratory, serologic testing, ultrasound and transient elastography (TE). In both patient groups, quantitative HBs antigen (HBsQ), alanine aminotransferase (ALT), hepatitis B virus deoxyribonucleic acid (HBV DNA) and liver fibrosis were analyzed. Results: The value of HBsQ is significantly higher in patients with HBeAg negative CHB 2477.02±4535.44 IU/ml than in the IC group 8791±11891 IU/ml; Z=3.32, p<0.001 (p=0.0009). In IC patients, 1 (4.76%) had fibrosis and 20 (95.24%)) did not have fibrosis. Out of 23 patients with HBeAg negative chronic hepatitis B, 8 (34.78%) had fibrosis and 15 (65.22%) did not have fibrosis. Patients with HBeAg negative hepatitis B had significantly higher liver fibrosis than IC; Fisher Exact Test p<0.05 (p=0.02). The increase of HBsQ for one single unit (IU/ml) does not have predictive value for fibrosis (Ext (B) =1.00), 95% C.I. for EXP (B): 1.00-1.00 / p>0.05. Conclusion: Quantitative hepatitis B surface antigen has intermediate weak statistically insignificant prediction for liver fibrosis R=0.25 (p<0.10).
Keywords: chronic hepatitis B; quantitative HBsAg; HBe antigen; HBV DNA